2022
DOI: 10.1126/sciadv.add0922
|View full text |Cite
|
Sign up to set email alerts
|

Real-time single-molecule observation of chaperone-assisted protein folding

Abstract: The ability of heat shock protein 70 (Hsp70) molecular chaperones to remodel the conformation of their clients is central to their biological function; however, questions remain regarding the precise molecular mechanisms by which Hsp70 machinery interacts with the client and how this contributes toward efficient protein folding. Here, we used total internal reflection fluorescence (TIRF) microscopy and single-molecule fluorescence resonance energy transfer (smFRET) to temporally observe the conformational chan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
2
3
0
Order By: Relevance
“…In contrast, we observed that DNAJA2 stabilized extended conformations of the TDP-43 LCD and suppressed its aggregation. This finding is in line with reports that HSP40s stabilize nonnative unfolded conformations of structured client proteins, leading to native-state folding (24,(60)(61)(62), and reports that DNAJA2 binds to the LCD (51). We also found that Hero11 stabilized the extended conformations of LCD of TDP-43 similarly to DNAJA2.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, we observed that DNAJA2 stabilized extended conformations of the TDP-43 LCD and suppressed its aggregation. This finding is in line with reports that HSP40s stabilize nonnative unfolded conformations of structured client proteins, leading to native-state folding (24,(60)(61)(62), and reports that DNAJA2 binds to the LCD (51). We also found that Hero11 stabilized the extended conformations of LCD of TDP-43 similarly to DNAJA2.…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, our detailed dynamics analyses indicate that Hero11 and DNAJA2 both stabilized the dwell times of the lowest FRET states (Figure 4C and D) while biasing for transition events between these lowest FRET states (Figure 4A and B) of the WT and A315T LCDs. For DNAJA2, this effect is consistent with the stabilization of unfolded client proteins by HSP40s (24,60,61). We also found that Hero11 has similar effects despite the lack of the structural features on HSP40 necessary for interaction with TDP-43 LCD (24,51).…”
Section: Hero11 and Dnaja2 Stabilize Conformationally Dynamic Extende...supporting
confidence: 81%
See 1 more Smart Citation
“…Clients FLUC ΔCys, K141C, K491C (with N-terminal 6x-His tag and C-terminal AviTag; referred to throughout as FLUC) was expressed and purified as previously described [53]. CLIC1 C24 (an isoform of CLIC1 harbouring mutations of five of the six native cysteines to alanines -C59A, C89A, C178A, C191A, C223A; the remaining cysteine C24 was not modified so it could be used for site-specific fluorescent labelling; this isoform is referred to as CLIC throughout), was expressed and purified as previously described [36].…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…Heath Ecroyd (University of Wollongong, Australia) presented work on the single-molecule fluorescence microscopy-based technique they developed to observe the interaction of molecular chaperone proteins with misfolded client proteins. 74 Using this technique, they have been able to observe the complete reaction cycle involved in Hsp70-mediated refolding of the model client protein, firefly luciferase, including multiple cycles of Hsp70 binding-and-release to an individual client protein. The work provides direct evidence for the unfoldase action of Hsp70 chaperones in facilitating client protein refolding.…”
Section: Chaperone Network Co-chaperones In the Stress Response And A...mentioning
confidence: 99%